A geographically diverse collection of schizosaccharomyces pombe isolates shows limited phenotypic variation but extensive karyotypic diversity - Brown, William R.A.; Litti, Gianni; Rosa, Carlos; James, Steve; Roberts, Ian; Robert, Vincent; Jolly, Neil; Tang, Wen; Baumann, Peter; Green, Carter; Schlegel, Kristina; Young, Jonathan; et al. (Genetics Society of America, 2011)
The fission yeast Schizosaccharomyces pombe has been widely used to study eukaryotic cell biology, but almost all of this work has used derivatives of a single strain. We have studied 81 independent natural isolates and 3 designated laboratory strains of Schizosaccharomyces pombe. Schizosaccharomyces pombe varies significantly in size but shows only limited variation in proliferation in different environments compared with Saccharomyces cerevisiae. Nucleotide diversity, p, at a near neutral site, the central core of the centromere of chromosome II is approximately 0.7%. Approximately 20% of the isolates showed karyotypic rearrangements as detected by pulsed field gel electrophoresis and filter hybridization analysis. One translocation, found in 6 different isolates, including the type strain, has a geographically widespread distribution and a unique haplotype and may be a marker of an incipient speciation event. All of the other translocations are unique. Exploitation of this karyotypic diversity may cast new light on both the biology of telomeres and centromeres and on isolating mechanisms in single-celled eukaryotes.